Hubungan Higiene Sanitasi dengan Kejadian Kecacingan Siswa Kelas III, IV, V SDN Kecamatan Tuntang Kabupaten Semarang : (Tahun Ajaran 2021/ 2022) - Pujiati Pujiati; Roro Kushartanti; Endah Widaningtyas (STIKES HAKLI Semarang, 2023)
Based on the 2020 worm survey in Semarang Regency, the prevalence of helminthiasis reached 65%–75% of the total examined samples. A preliminary survey in June 2021 involving 61 students of SDN showed that 29 children (47.5%) tested positive for worm eggs. This study aimed to identify the relationship between helminthiasis incidence and several risk factors, including hand washing habits, nail hygiene, defecation facilities at home, drinking water habits, type of household flooring, and food hygiene among elementary school students. The research employed a cross-sectional study design, where each subject was observed once and measurements were conducted at the time of examination. The study was carried out in June 2021 at the Gedangan Health Center, Semarang Regency. The study population consisted of grade 3 to 5 students at SDN , totaling 61 individuals, and the research involved the entire population. The analysis revealed that certain variables had significant associations with worm infection incidence. These included hand washing habits before and after eating as well as after defecation, nail hygiene, type of defecation facilities at home, type of household flooring, and food hygiene. In contrast, the habit of drinking water did not show any significant relationship with helminthiasis incidence. To reduce the prevalence of worm infections among elementary school students, several preventive measures were recommended. These included administering treatment to infected children, conducting regular deworming programs, and intensifying health promotion activities related to clean and healthy living behavior (PHBS). In particular, encouraging hand washing with soap before and after defecation was emphasized as a critical preventive practice. Furthermore, the role of school health programs (UKS) should be optimized to enhance children’s awareness of personal hygiene and health. This study highlights the importance of integrated school-based and community interventions to reduce worm infections and promote better health outcomes among students.